Single walled carbon nanotube incorporated Titanium dioxide and Poly (3-hexylthiophene) as electron and hole transport materials for perovskite solar cells - Siva, U.; Murugathas, T.; Yohi, S.; Natarajan, M.; Velauthapillai, D.; Ravirajan, P. (University of Jaffna, 2020)
This study focuses on incorporating single wall carbon nanotubes (CNTs) in both electron conducting por ous Titanium dioxide (TiO2) and the hole conducting Poly(3-hexylthiophene) (P3HT) layers in order to enhance the performance of perovskite solar cells. The CNT was incorporated at TiO2/CH3NH3PbIxCl3-x interface by dip coating TiO2 electrodes with CNT solution prior to deposition of CH3NH3PbIxCl3-x and by blending with P3HT, respectively. Raman spectra and Atomic Force Microscopic (AFM) images con firmed the presence of CNT in TiO2 electrodes and in P3HT, respectively. Optimized devices with the CNT show overall power conversion efficiencies (PCE) over 14%, under 100 mW/cm2 illumination with Air Mass 1.5 filter, which is 50% higher than that of the control device which is not having CNT. The enhancement is predominantly due to increase in short circuit current density (JSC) and fill factor, which resulted from surface passivation at the interface by CNT
Keywords: Perovskite; Solar cells; Carbon nanotube; TiO2; P3HT